Priming of dendritic cells by DNA-containing extracellular vesicles from activated T cells through antigen-driven contacts - Daniel Torralba (Nature Portfolio, 2018)
T cells are activated by antigen-bearing dendritic cells (DC), but how DCs receive reciprocal activating signals from T cells is still unclear. Here the authors show that mitochondrial DNA-containing extracellular vesicles from activated T cells can prime DCs for anti-viral immunity via the cGAS/STING DNA sensing pathways.